An Analysis of Students’ Higher Order Thinking Skills Through the Project-Based Learning Model on Science Subject (Department of Physics, Faculty of Mathematics and Natural Sciences, 2023)
The learning and assessment process that is oriented towards Higher Order Thinking Skills (HOTS) is a very urgent task for teachers in schools today. But in practice, the teacher cannot suddenly give an assessment with the HOTS system if the teacher has never been familiar with the HOTS-oriented learning model in the daily learning process. Teachers must carefully design HOTS-based learning and assessment, starting from the preparation, implementation, and evaluation stages based on the revised 2013 Curriculum. The project-based learning model is a learning model that is able to facilitate students in solving problems and higher-order thinking processes. Therefore, the focus of this research is to describe students' higher order thinking skills through a project-based learning model in science subjects at SMPN 33 Makassar. This study used a pre-experimental study with a One-Group Pretest-Posttest design. The sample in this study were 114 students at the junior high school level. The results showed that there was an increase in students' HOTS test scores from the pretest, posttest stage one and posttest stage two. This shows that the project-based learning model contributes to increasing the HOTS of SMPN 33 Makassar students in science subjects. Especially in the aspect of Physics.